1995
DOI: 10.1097/00019514-199503020-00006
|View full text |Cite
|
Sign up to set email alerts
|

Managing Critical Pathway Variances

Abstract: As the use of critical pathways expands at an increasing rate, we are faced with the issue of how to manage variances from the pathway. Variance management is not clearly defined in the literature, and many institutions search for the best approach. We have implemented a number of different techniques for variance management at Fletcher Allen Health Care. Our success benefits both patients and providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…20,21 Variances represent the discrepancies between planned and actual events. They can also represent outcomes that differ from those anticipated or deviations from the projected timeline.…”
Section: Variance Reporting and Analysismentioning
confidence: 99%
“…20,21 Variances represent the discrepancies between planned and actual events. They can also represent outcomes that differ from those anticipated or deviations from the projected timeline.…”
Section: Variance Reporting and Analysismentioning
confidence: 99%
“…2 The analysis of pathway variance is vital to achieving expected patient outcomes, the timely discharge of patients, and the appropriate utilization of resources. 8 The minute management of variance is important to maintain the quality of the clinical pathway and care. Our institution established a clinical pathway according to the Gantt chart from the beginning, and adopted a paper-based system for collecting date on variance.…”
Section: Discussionmentioning
confidence: 99%
“…Coffey et al reported that the timely analysis and management of variance from a critical pathway can bring about improvements in the form of fewer complications and less resource consumption. 8,9 Members of a multidisciplinary team review the charts at irregular intervals, collect data to analyze variances retrospectively, and strive to improve the management process; however, managing variance also requires ongoing perseverance and dedication, and it remains unclear how often teams should meet and what improvements need to be implemented. 8 According to clinical pathway maintenance, it is rarely discussed literally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations